Assessment of Shave Removal Without Further Excision in the Treatment of Spitz Nevi: A Retrospective Study of 58 Cases. Issue 2 (March 2020) - Nawrocki, Shiri; Mikhail, Nagy; Ghotb, Sara; Maghari, Amin
Background: Spitz nevi (or tumors) are noncancerous growths that are found particularly in the pediatric population. Their histologic features overlap with melanoma, but they have a favorable prognosis, even when showing atypical features. Objectives: The aim of this research is to examine whether Spitz nevi can be sufficiently removed by adequate shave excisions without a subsequent excision. Methods: Melan-A stained shave removal specimens (SRS) were obtained for 58 consecutively diagnosed Spitz nevi, along with slides of their postshave excision specimens. The SRS were reviewed for negative (clear) margins, defined as no neoplastic melanocytes detected within <0.2 mm of the deep and lateral margins of the specimen. Postshave excision specimens were reviewed for residual or recurrent lesions. Results: The 15 shave excision specimens with negative margins had no corresponding residual lesions on postshave specimens. There were no recurrences in any of the cases in an average of 17 months of follow-up. Conclusions: Observation may be a logical approach for the management of Spitz nevi when shave removal achieves clear margins and the lesion lacks atypical features.